Gender dimensions of agriculture, poverty, nutrition and food security in Nigeria - Ajani, Olubunmi Idowu Yetunde (International Food Policy Research Institute, 2009)
Gender analysis focuses on the different roles and responsibilities of women and men and how these affect society, culture, the economy and politics. For example, important differences exist between women and men in their quality of life; in the amount, kind and recognition of work they do; in health and literacy levels; and in their economic, political and social standing. Women are too often marginalized in their families and their communities, suffering from a lack of access to credit, land, education, decision-making power and rights to work. Explicitly, while gender analysis focuses on the relations between men and women, such analyses including the ones that will later be cited in this paper, disproportionately find that women have less access to, and control of, resources than men which is why this paper emphasizes the role of women, and their well-being in agriculture, nutrition and food security. Not surprisingly, women therefore comprise the majority of the world’s poor in both the urban and rural sectors and the majority of those working in the informal sector (Spieldoch 2007). There are 450 million women and men working as agricultural laborers worldwide who do not own or rent the land on which they do not work nor the tools and equipment they use. These workers comprise over 40 percent of the world‘s agricultural labor force often living below the poverty line and forming part of the majority of the rural poor in many parts of the world (FAOILO-IUF 2005). The number of waged female agricultural workers, currently at 20-30 percent of the waged workforce is increasing (Spieldoch 2007). According to the United Nations (2006), women are responsible for over half the world’s food production. In developing countries, rural women produce between 60-80 percent of the food and are the main producers of the world’s staple crops (such as rice, wheat, maize), which provide up to 90 percent of the rural poor’s food intake. Women dominate the production of legumes and vegetables in small plots, raise poultry and small animals and provide most of the labor for post-harvest activities such as storage, handling and processing of grains. The Food and Agricultural Organization (FAO) indicates that women produce as much as 80 percent of the basic foodstuffs for household consumption and sale in Sub-Saharan Africa (FAO-ILO-IUF 2005). According to Huston (1993), women share of food production in Africa is estimated at 80 percent while Mijindadi (1993) asserted that in Nigeria women are responsible for about 70 percent of actual farm work and constitute up to 60 percent of the farming population.